O. W. Martyszyn, Politiczeskije wzgljady Mohandasa Karamczanda Gandhi - Justyński, Janusz (Czasopismo Prawno-Historyczne, 1972)
Recenzja: O. W. Martyszyn, Politiczeskije wzgljady Mohandasa Karamczanda Gandhi, Moskwa 1970.